Lunar and solar tidal variabilities in mesospheric winds and EEJ strength over Tirunelveli (8.7°N, 77.8°E) during the 2009 major stratospheric warming - Sathishkumar, S.; Sridharan, S. (My University, 2013)
Mesospheric wind observations by the medium frequency radar and geomagnetic field observations at Tirunelveli (8.7°N, 77.8°E, 1.75°N dip angle) are used to study the relative importance of solar and lunar influences in the variabilities of mesospheric tides and equatorial electrojet (EEJ) strength during the unprecedented major stratospheric sudden warming (SSW) of 2009. It is observed that the afternoon reversal in the EEJ, popularly known as counter electrojet, occurs consecutively for several days during the SSW event, when there is an enhancement of solar semidiurnal tide in both zonal wind at 90 km and EEJ strength over Tirunelveli. Although the amplitude of lunar tides also shows enhancement, it is much less than that of solar. The diurnal tidal amplitude in zonal wind and EEJ strength also shows large enhancement just before the onset of SSW. However, solar semidiurnal tide dominates diurnal tide during the SSW. The diurnal tidal phase in zonal wind shifts to a few hours earlier during the SSW. The lunar semidiurnal tidal phase shifts to later hours in both zonal wind and EEJ strength. The main observation of the present study is that the large semidiurnal tide observed during the SSW 2009 is mostly solar driven and only partly lunar driven, although tidal planetary wave interaction also may play a vital role. Although a similar behavior is noticed during the SSW 2006 also, the large lunar semidiurnal tide observed in the EEJ strength without having large lunar semidiurnal tide in the underlying mesospheric winds needs further investigation.
Keywords: Solar tidal; Mesospheric winds; Equatorial electrojet; Stratospheric sudden warming; Tirunelveli; EEJ; SSW